L'Ossessione del Segno - Pozzati, Maura (Verona : Studio La Città, 1996)
Arcangelo ; Arends, Stuart ; Baselitz, Georg ; Brown, James ; Caccioni, Luca ; Calvini, Laura ; Carrà, Carlo ; Carroll, Lawrence ; Chia, Sandro ; Cucchi, Enzo ; Cuniberti, Pierachille ; Casa, Mattia Della ; De Chirico, Giorgio ; De Pisis, Filippo ; Dorazio, Piero ; Fontana, Lucio ; Gallo, Giuseppe ; Gardini, Luisa ; Gastini, Marco ; Gorky, Arshile ; Grosz, George ; Hartung, Hans ; Kline, Franz ; Licini, Osvaldo ; Mafai, Mario ; Manai, Piero ; Manfredini, Giovanni ; Marini, Marino ; Martini, Arturo ; Melotti, Fausto ; Merz, Mario ; Morandi, Giorgio ; Novelli, Gastone ; Paladino, Mimmo ; Pessoli, Alessandro ; Pozzati, Concetto ; Pizzi Cannella, Piero ; Roma, Carol ; Savinio, Alberto ; Scanavino, Emilio ; Shifano, Mario ; Semeghini, Pia ; Severini, Gino ; Sironi, Mario ; Stamm, Ted ; Stockholder, Jessica ; Tagliatti, Ketty ; Tancredi ; Tuttle, Richard ; Twombly, Cy ; Vedova, Emilio ; Verna, Claudio ; Viani, Lorenzo ; Violetta, Antonio ; Walker, John
L'Ossessione del Segno, Studio La Città, Verona, 7 dicembre '96 - 30 gennaio '97. Mosta n. 187
Italiaans & Engels
kunstcatalogus